Machiavellianism, emotional manipulation, and friendship functions in women's friendships. (January 2016) - Abell, Loren; Brewer, Gayle; Qualter, Pamela; Austin, Elizabeth
Abstract: Machiavellianism and emotional manipulation has not been investigated in friendships. The current studies investigated Machiavellianism, emotional manipulation, and six friendship functions in women's same-sex friendships. For study 1, women ( N  = 221) completed the Mach IV, emotional manipulation measure (with reference to their own behaviour and their friend's behaviour), mood worsening and use of inauthentic displays from the managing emotions of others scale, and the friendship function measure. Machiavellianism predicted the self-perceived ability to employ emotional manipulation towards a same-sex friend and perceiving their friend to use emotional manipulation towards them. Machiavellianism predicted lower scores on all six friendship functions. For study 2, women ( N  = 186) completed the Mach IV, the modified emotional manipulation measure (with reference to their own behaviour and their friend's behaviour), and the friendship function measure. Women high on Machiavellianism reported using emotional manipulation more frequently towards their same-sex friend and perceived their same-sex friend to frequently use emotional manipulation towards them. Machiavellianism predicted lower scores on five of the friendship functions. These studies demonstrated that women higher on Machiavellianism employ emotional manipulation in their same-sex friendships. Women with higher Machiavellianism scores also perceived that they themselves were manipulated by their friend. Highlights: Women with higher Machiavellianism scores reported the ability to emotionally manipulate their same-sex friend. Women with higher Machiavellianism scores frequently employed emotional manipulation towards their same-sex friend. Women with higher Machiavellianism scores perceived their same-sex friend to use emotional manipulation towards them. Machiavellianism was associated with decreased scores on five friendship functions.